Antioxidative mechanisms protect resistant strains of Staphylococcus aureus against ciprofloxacin oxidative damage - Paez, Paulina Laura (2010)
The aim of this investigation was to determine whether the antioxidant defences protect resistant strains of Staphylococcus aureus against ciprofloxacin oxidative damage. Reactive oxygen species (ROS) were determined by chemiluminescence and nitric oxide (NO) was assayed by Griess reaction. The accumulation of ciprofloxacin was examined by fluorometry and oxidation of protein, catalase, ferrous reduction antioxidant potency (FRAP), carbonyls and advanced oxidation protein products (AOPP), studied by spectrophotometry. Ciprofloxacin stimulated higher production of ROS and NO in the susceptible strains than in the resistant ones. There was higher accumulation of antibiotic in sensitive strains than in resistant ones, except for the most resistant strain, which accumulated an elevated amount of antibiotic. The FRAP/ciprofloxacin accumulation ratio of the antibiotic was lower in sensitive than in resistant strains. The most resistant strain exhibited the highest FRAP and presented a high catalase activity. There was oxidation of proteins in the presence of ciprofloxacin, with the carbonyl residues increasing in sensitive and resistant S. aureus. The degradation of carbonyls to AOPP in oxidized proteins was higher in the resistant than in sensitive strains. In conclusion, an increase in antioxidant capacity and a rapid oxidation of carbonyls to AOPP contributed to resistance to ciprofloxacin.